EKSTERNALITAS PENETAPAN KEBIJAKAN PAJAK KARBON DI INDONESIA - Hubah, Sonia Vitania (MEDIA RISET EKONOMI [MR.EKO], 2023)
The purpose of this study is to determine the impact of the Carbon Tax policy in reducing negative externalities in Indonesia, and to find out the comparison between the planned Carbon Tax policy in Indonesia and other countries in the world. The type of research used is qualitative research. The research method used is a literature study with data sources in the form of secondary data. The secondary data used is sourced from books, journals, government regulations, and internet sites. The results showed that the establishment of a Carbon Tax policy can reduce negative externalities due to carbon emissions. In addition, with this policy, state revenue from taxes can increase. In Indonesia, the establishment of the Carbon Tax policy is planned to be implemented in 2025 with a lower tax rate compared to other European countries that have implemented Carbon Tax policies. In these European countries, the establishment of Carbon Tax policies has been proven to reduce negative externalities in the environment due to carbon emissions.